Functional polarization of human hepatoma HepaRG cells in response to forskolin. Issue 1 (December 2018) - Mayati, Abdullah; Moreau, Amélie; Le Vée, Marc; Bruyère, Arnaud; Jouan, Elodie; Denizot, Claire; Parmentier, Yannick; Fardel, Olivier
Abstract HepaRG is an original human hepatoma cell line, acquiring highly differentiated hepatic features when exposed to dimethylsulfoxide (DMSO). To search alternatives to DMSO, which may exert some toxicity, we have analyzed the effects of forskolin (FSK), a cAMP-generating agent known to favor differentiation of various cell types. FSK used at 50 µM for 3 days was found to promote polarization of high density-plated HepaRG cells, i.e ., it markedly enhanced the formation of functional biliary canaliculi structures. It also increased expressions of various hepatic markers, including those of cytochrome P-450 (CYP) 3A4, of drug transporters like NTCP, OATP2B1 and BSEP, and of metabolism enzymes like glucose 6-phosphatase. In addition, FSK-treated HepaRG cells displayed enhanced activities of CYP3A4, NTCP and OATPs when compared to untreated cells. These polarizing/differentiating effects of FSK were next shown to reflect not only the generation of cAMP, but also the activation of the xenobiotic sensing receptors PXR and FXR by FSK. Co-treatment of HepaRG cells by the cAMP analog Sp-5, 6-DCl-cBIMPS and the reference PXR agonist rifampicin reproduced the polarizing effects of FSK. Therefore, FSK may be considered as a relevant alternative to DMSO for getting polarized and differentiated HepaRG cells, notably for pharmacological and toxicological studies.